Functional genre transformations of modern philosophizing: the innovative potential of the genre of confession - Антіпова, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
Functional genre transformations of modern philosophizing are described. The innovative potential of the genre of confession is revealed in the context of globalization processes. The representational possibilities of revelation as a means of sociocultural self-identification of an individual are analysed.